Peranan Pemimpin Informal dalam Meningkatkan Partisipasi Masyarakat dalam Pembangunan di Desa Malola - Liow, Michael Rojer; Laloma, Alden; Pesoth, Welly (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Informal leaders are legitimate is not the leader/legality in Government, but the informal leaders are part of the villagers whose role is crucial in giving influence to the residents of the village. the role of informal leaders does not appear, this is because the formal leader of the village head is not too empowering the role of informal leadership. the purpose of this research is to know the role of the Informal Leader in improving community participation in development in the village Research methods used in this study is a qualitative method of analysis is the efforts made by way of working with data, organizing data, sifting through data into units that can be managed, menyintesiskan data, search for and find patterns, find what is important and what is learned, and decide what can be told to others. The results of this research show that the informal leader's role in improving public participation is very important amongst the people, but not too effective in terms of informing and invites the public to take part in development activities to increase the participation of community development need for sinerginitas between formal and informal leaders leaders Keword: Informal leaders, community participation in development